Scientific expedition "Life in ice" : August 2002 - August 2003, observations at Kinnvika ( 80° 3’N, 18° 12’E ) Svalbard, Nordaustlandet - Trinks, Hauke (2003)
A scientific expedition of the Technical University of Hamburg-Harburg (TUHH) was performed in 2002/03 on Nordaustland, Svalbard. Two humans with two sledge dogs stayed continuously for thirteen months in a little hut at a latitude of 80°N. Using a small, well equipped laboratory, many observations and measurements were performed and documented. The main purpose of the expedition was the systematical experimental investigation of the growth and melting of sea ice and it’s microstructure during the course of a whole year. Outgoing from the observations the hypothesis was confirmed about the function of sea ice at the very beginning of Life as a possible matrix to push prebiotic chemistry towards first biological processes. The gained results indeed deliver many arguments that Life may have started in the sea ice of the early Earth, four billion years ago. Sea ice shows a complicated microstructure containing about 10 14 tiny compartments per cubic metre between which liquid brine drips and mineralic particles, as well as small gas bubbles, are embedded. This environment may support chemical reactions leading finally to primitive life. Outgoing from the investigations of the real sea ice at Nordaustland, a model conception is derived concerning sea ice as a biochemical reactor. The construction of a corresponding technical sea ice reactor is described. With that, future further realistic experimental investigations are possible, which may be performed in the laboratory using artificially produced sea ice. Sea ice is a favourable environment for the existence of many micro-organisms. Particularly it seems that various bacteria prefer to live in sea ice. During the expedition, in a systematical way, samples of these bacteria were taken each month, which grew in special containers frozen in sea ice. The bacteria samples were sent to the Biotechnological Institute of TUHH where they will be investigated concerning the bacteria’s genetic structure. Many kinds of new bacteria were already identified. Some of these may ...